2014
DOI: 10.1371/journal.pone.0099904
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pattern of the Acute Phase of Subarachnoid Hemorrhage in a Novel Porcine Model: Studies with Cerebral Microdialysis with High Temporal Resolution

Abstract: BackgroundAneurysmal subarachnoid hemorrhage (SAH) may produce cerebral ischemia and systemic responses including stress. To study immediate cerebral and systemic changes in response to aneurysm rupture, animal models are needed.ObjectiveTo study early cerebral energy changes in an animal model.MethodsExperimental SAH was induced in 11 pigs by autologous blood injection to the anterior skull base, with simultaneous control of intracranial and cerebral perfusion pressures. Intracerebral microdialysis was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…As described in the previously published material [ 17 ], there were two different patterns in the animals after SAH induction. In nine animals, ICP and CPP were restored towards pre-injury levels shortly after SAH induction followed by a gradual slow increase in ICP during the rest of the monitoring time.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As described in the previously published material [ 17 ], there were two different patterns in the animals after SAH induction. In nine animals, ICP and CPP were restored towards pre-injury levels shortly after SAH induction followed by a gradual slow increase in ICP during the rest of the monitoring time.…”
Section: Resultsmentioning
confidence: 97%
“…Experimental SAH was induced in pigs, a detailed description of this procedure has been previously published [ 17 ]. 11 pigs under general anesthesia underwent experimental SAH by autologous blood injection to the anterior skull base.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, craniotomy has been used to reach the MCA territory [ 216 , 217 ], the suprasellar subarachnoid cistern [ 218 , 219 , 220 ], and between the crests of the superior frontal and motor gyri [ 157 ]. Basal subarachnoid cisterns have also been reached through burr holes directed to the anterior skull base [ 214 , 215 ], in studies that exhibit the impact of transient ischemia derived from the SAH. Finally, a recent study showed that the subarachnoid space could be achieved precluding craniotomy, through the direct transorbital injection of blood into the interpeduncular cistern, without eye enucleation [ 213 ].…”
Section: Interventions To Induce Hemorrhagic Strokes In Pigsmentioning
confidence: 99%
“…Cerebral microdialysis enables bedside analysis of the chemistry of the extracellular space. [ 15 ] The analysis of the absolute values and ratios of lactate and pyruvate can help in early detection of metabolic crisis;[ 16 18 ] however, microdialysis is an invasive technique, and data obtained are truly representative only of the local tissue milieu. An external ventricular drain (EVD) is often already in place in patients at high risk for the development of symptomatic vasospasm due to concomitant development of hydrocephalus from larger volumes of SAH and intraventricular hemorrhage.…”
Section: Introductionmentioning
confidence: 99%